Analisis Sikap Orangtua dan Guru Terhadap Sistem Pembelajaran Daring Di Era Covid-19 Untuk Siswa Berkebutuhan Khusus Di SLBN 1 Makassar (Perspektif Pedagogis, Psikologis, dan Sosiologis) - Abdul Hadis; Djoni Rosyidi; Ponijo Ponijo (Seminar Nasional LP2M UNM, 2021)
Abstrak. The problem of this research is at covid-19 era of online instruction system for special need students is monoton this bacause students is not learning interest and motivation. The goal of this research is analyzed teacher and parents to online instruction system in Covid-19 Era for special need students in sociologis, psychologis, and paedagogis perspective. Method of this research is attitude of teachers and parents as single variable, design of this research is descriptive, amount of sample ia 10 teacher and 10 parents determined purposive random sampling technique, location of this research is SLBN 1 Makassar, instrument and data collective technique is questionnaire, data analysis technique with percentage descriptive analysis. The result and conclusion of this research is 100 % teachers and parents is positive attitude toward online instruction system in paedagogis perspective, and 100 % of teachers and parent is negative attitude toward online instruction system in sociologist and psychologist perspective. Kata Kunci: Sikap Orangtua, Guru, Daring, Paedagogis, Psikologis, Sosiologis